Earnings Quality: Impact of Factors with Firm Size as Moderating Variable - Darmadi, Eliezer Elbert; Susanto, Yulius Kurnia (Media Ilmiah Akuntansi, 2024)
This research objective is to obtain empirical evidence about the effect of liquidity, leverage, investment opportunity set (IOS), independent commissioner, institutional ownership, profitability, profit on earnings quality and the moderation effects of company size on interaction between profitability with earnings quality and profit growth with earnings quality. The researcher used purposive sampling method and determined 62 companies met the sampling criteria from population that is manufacturing company listed in Indonesia Stock Exchange from 2017 - 2021. The result obtained from moderated regression shows that liquidity, leverage, IOS, independent commissioner, institutional ownership, profitability, profit growth and firm size have no significant effect on earnings quality, and also company size does not moderate the effect of profitability and profit growth on earnings quality. The result shows that company size does not relevant on affecting the quality of earnings of a company.